A Juridical Review Of The Shooting On The Spot Conducted By The Police Against The Perpetrator Criminal Act Of Theft - Malik Abdillah Dahil (Estudiante Law Journal, 2019)
This research presents an overview of how juridical reviews of shooting in the place conducted by the police against perpetrators of criminal theft and the obstacles faced by the police in shooting in the place against criminals. This type of research uses normative research methods with the help of empirical data. In this case, the researcher combines elements of normative law which are then supported by the addition of data or empirical elements.The results of this study show that the actions taken by the police against the alleged perpetrators of motorcycle theft are not discretionary but pure criminal acts such as serious crimes of persecution that result in death or murder if the police investigators perform actions that are not following operational standards of procedure in the use of power with firearms or have exercised discretionary authority that goes beyond the limit of authority (abuse of power). The factors that are the constraints of the police in shooting in the place of the perpetrators of crime are the level of public crowds, the distance of the shooting with the perpetrator, weather conditions.Keywords: Shoot On The Spot, Police, Theft.